El estrés materno como factor de riesgo para fisuras labio-palatinas - Nazer H., Julio; Finschi P., Andrés; López-Camelo, Jorge; González G., Gisella (Revista Hospital Clínico Universidad de Chile, 2016)
Introduction: several studies have shown an association between stress caused by natural disasters, acts of terrorism and war, which have been corroborated by experimental studies in rats, with presence of oral clefts (FO) in the children of women who suffered stress in the first weeks of pregnancy. Objectives: To demonstrate the relationship between stress caused by the earthquake and tsunami that struck the central and south regions of Chile, on February 27, 2010 and the prevalence rate of FO in the disaster area. Material and Methods: Registration of ECLAMC (Latin American Collaborative Study of Congenital Malformations) Period 2000- 2011. With this information we created two groups: Group 1: Children born before the event, from 2002 to 2009 up to 6 months after earthquake, that means August 2010. Group 2: the postearthquake period, from the seventh month after the earthquake (September) until the end of 2011. Results: the prevalence of oral clefts of the first group was 0.88 per thousand births (0.57 for cleft lip and cleft palate 0.30) .and the second group of 1.07 per thousand, (0.70 cleft lip and cleft palate 0.37) statistically significant difference (p <0.05). Conclusion: There is a positive, significant association between maternal stress and the risk of having children with FO.